Correction: Awahara et al. The Effects of Side-Chain Configurations of a Retro–Inverso-Type Inhibitor on the Human T-Cell Leukemia Virus (HTLV)-1 Protease. Molecules 2022, 27, 1646 - Chiyuki Awahara; Daiki Oku; Saki Furuta; Kazuya Kobayashi; Kenta Teruya; Kenichi Akaji; Yasunao Hattori (Molecules)
Figure Legend [...]